Persepsi Siswa/i SMA Negeri 4 Singaraja Terhadap Perpustakaan Sekolah yang Ideal - Devita, Amanda (ACARYA PUSTAKA, 2024)
This study aims to (1) find out the perception of students of SMA Negeri 4 Singaraja towards the Graha Pustaka Library of SMA Negeri 4 Singaraja. (2) To find out the perception of students of SMA Negeri 4 Singaraja regarding the ideal school library. The research method used is a qualitative descriptive research method with a purposive sampling technique for collecting informants. This research took place in the Library of SMA Negeri 4 Singaraja. Data collection in this study uses observation techniques, interviews, and document studies. The result of this study is that most of the students of SMA Negeri 4 have a good perception of the school library of SMA Negeri 4 Singaraja. According to them, the library of SMA Negeri 4 Singaraja has a good collection, but the novel collection is less diverse, the library space is strategic and comfortable, the service and librarians who serve in a friendly manner. In addition, most students of SMA Negeri 4 Singaraja have the perception of an ideal school library, namely a library that has a complete and diverse collection with a strategic and comfortable room, which is managed by friendly and professional management personnel so that it is maximum in providing services to its students. Keywords: School Library, Ideal Library, Perception, Students